Achieving supply chain agility : information system integration in the chinese automotive industry - Wu, Yi 1981- (Palgrave Macmillan, 2019)
This book identifies factors of information system (IS) integration that influence supply chain agility and illustrates how IS integration can achieve greater supply chain agility. Also considering the consequent operational impacts that arise from IS-enabled supply chain agility, the author presents real-life examples through interviews and surveys to explore how IS integrations affect supply chain agility in the context of the Chinese automotive industry. The ability to swiftly respond to competitive challenges is a key element in industry 4.0 and organisations with agile supply chains are better prepared to respond to uncertainties and changes. This book develops and presents guidelines on the deployment of information system integration in order to achieve efficient agile supply chains.